Chaotic True Random Number Generator for Secure Communication Applications - Al-Shidaifat, Alaaddin; Jayawickrama, Chamindra; Jung, Yechan; Songwook-Lee; Song, Hanjung; Kahrama, Nihan (IEEE, 2020)
This work is proposed chaotic true random number generator (TRNG) based on chaotic PWM sequence generator. The chaos CMOS circuit presents here is the chaotic sequence generator. The main components of the chaotic PWM circuit is chaotic sequence generator for chaotic triangular waveforms. The chaotic TRNG was designed by using 0.18 mu m CMOS process. The full system is prose to be a implementation of IoT secure data communication system using chaotic security.
Keywords: chaos; TRNG; chaotic sequence; EMI; MODULATION; REDUCTION; Engineering